2011
DOI: 10.1002/biot.201000254
|View full text |Cite
|
Sign up to set email alerts
|

Dead cell counts during serum cultivation are underestimated by the fluorescent live/dead assay

Abstract: The live/dead fluorescent assay provides a quick method for assessing the proportion of live and dead cells in cell culture systems or tissues and is widely used. Dead cells are detected by the fluorescence produced when propidium iodide (PI) binds to DNA; PI and similar molecules are excluded from live cells but can penetrate dead cells because of their loss of membrane integrity. Here we investigated the effect of serum in the culture medium on the reliability of the method. We assessed viability of chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Starting from the 7 th DIV until the end of experiment, OHCs were maintained in the serum-free media [34, 86, 88] in order to decrease glial activation, proliferation and scar formation [79, 89]. As described below, PI uptake measurements were also performed in serum-free media as DNase I present in the serum can degrade the DNA of dead cells and lead to an inaccurate estimate of the number of dead cells [90]. …”
Section: Methodsmentioning
confidence: 99%
“…Starting from the 7 th DIV until the end of experiment, OHCs were maintained in the serum-free media [34, 86, 88] in order to decrease glial activation, proliferation and scar formation [79, 89]. As described below, PI uptake measurements were also performed in serum-free media as DNase I present in the serum can degrade the DNA of dead cells and lead to an inaccurate estimate of the number of dead cells [90]. …”
Section: Methodsmentioning
confidence: 99%
“…Qualitatively, the cell viability was determined with vital staining using calcein AM (Sigma) and Propidium Iodide (PI) as described elsewhere [26][27][28]. Therefore, 5 mm  5 mm decellularized pieces (as described in 2.7) of the vessels were put into a dye solution, consisting of 3 lM Calcein AM (live) and 3 lM PI (dead) dissolved in EGM-2 expanding growth culture medium and incubated for 30 min at room temperature (RT).…”
Section: Live/dead Cell Viability and Immunostainingmentioning
confidence: 99%
“…However, reports of severe complications derived from the use of intra-articular local anaesthetic pumps after orthopaedic surgery have renewed the interest in these drugs. [1][2][3] The potential for cartilage damage due to toxicity of intra-articular local anaesthetics is particularly concerning and it has been the focus of recent studies. 1,2 Most studies indicate that the toxic effect is drug and time dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that long-term exposure to bupivacaine is chondrotoxic. 1,3,5,7,8 Moreover, several recent studies have demonstrated that even a brief exposure to bupivacaine may be chondrotoxic. 6 Other drugs, such as levobupivacaine, have been shown to provide excellent intra-articular pain control.…”
Section: Introductionmentioning
confidence: 99%